2014
DOI: 10.1007/s00167-014-3144-9
|View full text |Cite
|
Sign up to set email alerts
|

A 3D finite element model to investigate prosthetic interface stresses of different posterior tibial slope

Abstract: The results suggested that the tibial component inclination might be favourable to 7°-10° so far as the stress distribution is concerned. The range of the tibial component inclination also can decrease the wear of polyethylene. Chinese posterior tibial slope is bigger than in the West, and the current domestic use of prostheses is imported from the West, so their demands to tilt back bone cutting can lead to shorten the service life of prostheses; this experiment result is of important clinical significance, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…The more natural kinematics of the knee, such as femoral external rotation and posterior translation during knee flexion, result in better functional outcome and satisfaction for the patient post-TKA [ 6 , 7 ]. The altered load-bearing pattern could be reflected by contact area and contact pressures that are related to aseptic loosening, which is the most common cause of surgical failure and prosthesis revision [ 8 10 ]. Stress shielding caused by the changed load-bearing patterns can subsequently result in bone remodeling, which is one of the main causes of prosthesis loosening [ 9 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The more natural kinematics of the knee, such as femoral external rotation and posterior translation during knee flexion, result in better functional outcome and satisfaction for the patient post-TKA [ 6 , 7 ]. The altered load-bearing pattern could be reflected by contact area and contact pressures that are related to aseptic loosening, which is the most common cause of surgical failure and prosthesis revision [ 8 10 ]. Stress shielding caused by the changed load-bearing patterns can subsequently result in bone remodeling, which is one of the main causes of prosthesis loosening [ 9 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Stress shielding caused by the changed load-bearing patterns can subsequently result in bone remodeling, which is one of the main causes of prosthesis loosening [ 9 , 11 ]. Excessive contact pressure may cause more wear of the polyethylene prosthesis, resulting in more debris and wear particles, which in turn can cause a biological response resulting in bone resorption and osteolysis that are also one of the main causes of prosthesis loosening [ 10 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggested that during TKA, orthopedic surgeons should minimize varus implantation of the tibial prosthesis as much as possible [9]. Shen et al evaluated the effect of four different posterior tibial slopes (0°, 3°, 6°, and 9°) of the tibial prosthesis on the contact pressure of the polyethylene liner, and found that the contact stress at 3°and 6°posterior slopes was almost uniformly distributed in the medial and lateral compartments, and the wear of the polyethylene was the lowest, indicating the importance of proper posterior tibial slope [11]. Osano et al analyzed the changes in the peak values of the mixed stress on the polyethylene liner when the tibial prosthesis was in neutral position (0°), 15°internal rotation, and 15°external rotation.…”
Section: Discussionmentioning
confidence: 99%
“…Shen et al analyzed the effect of the posterior slope angle of tibial prosthesis on the peak value of contact stress on the polyethylene liner. The results showed that the posterior slope of 3°or 6°of tibial prosthesis had a relatively small peak value of the contact stress [11]. The above studies analyzed the effect of only a single tibial prosthesis implantation parameter on the knee contact mechanics, which demonstrated a certain clinical significance for tibial prosthesis implantation.…”
Section: Introductionmentioning
confidence: 96%